2005
DOI: 10.1080/10428190500126380
|View full text |Cite
|
Sign up to set email alerts
|

The effect of absolute lymphocyte count recovery kinetics on survival after autologous stem cell transplantation for non-Hodgkin's lymphoma

Abstract: Absolute lymphocyte count (ALC) >or=500 cells/microl at day 15 after autologous stem cell transplantation (ASCT) is a powerful independent, prognostic indicator for survival in multiple hematological malignancies. A limitation in these studies was the selection of a single time point (day 15 post-ASCT) as the only discriminator of clinical outcome in relation to ALC recovery. We hypothesized there is a continuous and not discrete relationship between ALC recovery and clinical outcome post-ASCT in NHL. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…There are several reports suggesting lower risk of relapse and thus better PFS in patients with rapid lymphocyte recovery defined as the Optimizing blood graft content in auto-SCT E Jantunen and S Fruehauf absolute lymphocyte count on day þ 15 after stem-cell infusion. [28][29][30][31][32][33][34][35][36][37][38][39] These studies are summarized in Table 3. The number of lymphocytes within the graft infused seems to have prognostic significance potentially by affecting early lymphocyte recovery.…”
Section: Immunological Recovery Post Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports suggesting lower risk of relapse and thus better PFS in patients with rapid lymphocyte recovery defined as the Optimizing blood graft content in auto-SCT E Jantunen and S Fruehauf absolute lymphocyte count on day þ 15 after stem-cell infusion. [28][29][30][31][32][33][34][35][36][37][38][39] These studies are summarized in Table 3. The number of lymphocytes within the graft infused seems to have prognostic significance potentially by affecting early lymphocyte recovery.…”
Section: Immunological Recovery Post Transplantmentioning
confidence: 99%
“…62 Several studies suggest that the risk of infectious complications, especially those of viral origin, is increased in patients receiving CD34 þ cell selected grafts, [63][64][65][66] although not all studies have noted this association. 58,67,68 35 NHL 274 ALC-15 independent prognostic factor for PFS and OS Joao 36 NHL/MCL 42 ALC-15 an independent prognostic factor for PFS and OS Tiwari 37 NHL 268 no association with ALC-15 and DFS or OS Porrata 39 NHL 50 NK cell recovery independent predictor for survival Porrata 28 MM 126 ALC-15 associated with better PFS and OS Hiwase 38 MM 119 ALC-30 associated with better PFS and OS Porrata 33 AL 145 ALC-15 independent prognostic factor for PFS and OS Nieto 31 MBC Optimizing blood graft content in auto-SCT E Jantunen and S Fruehauf…”
Section: Tumour Cell Contamination Of the Graftmentioning
confidence: 99%
“…1 Predictors of post transplant outcome include performance status, time from diagnosis to relapse or transplant, and chemosensitivity to salvage therapy. 2 Early lymphocyte recovery measured by an absolute lymphocyte count (ALC) 4500/ml obtained on day 15 post transplant is independently associated with favorable outcomes after autografting for NHL, [3][4][5] multiple myeloma, 3 Hodgkin's disease, 5,6 acute myeloid leukemia 7 and metastatic breast cancer. 8,9 Myeloid growth factors are often administered after hematopoietic cell transplantation to accelerate neutrophil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the importance of lymphocyte kinetics has been found in NHL patients undergoing AHCT. 13 A previous study 14 has demonstrated an association between the pre-apheresis ALC and the quantity of lymphocytes in the stem cell product that in turn influenced the ALC-15 value. We did not find any association between the pre-apheresis ALC and the ALC-15 nor the ALC-90.…”
Section: Discussionmentioning
confidence: 99%